Advancing women entrepreneurship in a developmental state: an agenda for higher education institutions - Ademola Olumuyiwa Omotosho; Kimanzi Mathew; Alfred Modise; Ayansola Ayandibu (Cogent Education, 2024)
AbstractSouth Africa’s public sector has launched a variety of gender-focused schemes aimed at empowering women entrepreneurs over the years. However, emerging literature suggests that the efficacy of these programmes is constrained. Consequently, alternative approaches might be needed to address women entrepreneurs’ concerns. Previous studies have not explored the potential of higher education institutions as custodians of knowledge and innovation to promote female entrepreneurship in the country. As a result, this study employs a semi-systematic literature review to explore the influence of stakeholders’ initiatives in advancing women’s entrepreneurship in South Africa. Additionally, the Web of Science database was utilised, which initially yielded 82 articles, after applying exclusion criteria, 53 papers were obtained as the final corpus. The research findings indicate that the South African government, at various levels, has vibrant programmes and initiatives geared toward developing women’s entrepreneurship; however, these programmes’ effectiveness is perpetually undermined by several underlying bottlenecks as highlighted in this study. Moreover, the findings reveal that government initiatives are at the forefront of women’s empowerment efforts and that higher education institutions play a peripheral role. To motivate the higher education sector to embrace its role as an agent of change in society, the authors concluded the paper by proposing a university-based women’s entrepreneurship framework. The proposed framework, which prioritizes female inclusivity in the context of higher education, has the potential to cultivate an environment conducive to nurturing entrepreneurial aspirations in women.